Object-Oriented Approach and Distributed Finite Element Simulations - Breitkopf, Piotr; Escaig, Yves (European Journal of Computational Mechanics, 1998)
We present an application of object-oriented approach in the context of distributed computing in the field of structural engineering problems. In this work, conducted within the framework of a general purpose finite element code, we consider two types of distributed algorithms: the cooperation of heterogeneous computing systems and an algorithm for distributing the resolution of the finite element problem. In the first case, the major issue is the transparent distribution of the data base involving data structures and algorithms. In the first part of the present work, we present DDSM (Distributed Data Structures Manager) dealing with this first issue. The second case addressed is that of solution of linear systems by a domain decomposition direct method. Performance results given are those of a Cray T3D system. Communications and process control are implemented using the PVM library.